Legal Breakthrough on Bank Secrets in Banking to Prevent and Rate the Crime of Money Laundry - Sinaga, Esron; Sunarmi; Mahmud Mulyadi (International Journal of Law Analytics, 2023)
In the banking world, the term bank secrecy is often an interesting topic for debate among academics, practice owners, and politicians. This is due to the curiosity of the public whether the bank is healthy or not, problematic or not, but on the other hand, the bank is unlikely to want to provide information to the public because it collides with bank secrecy as regulated in article 1 (paragraph) 28 of Law Number 10 of 1998 concerning the prevention and eradication of money laundering, which reads bank secrecy is everything related to information regarding depositors and their deposits. And Article 40 (paragraph) 1 Law Number of 1998 concerning banking. This research was conducted by examining library materials which is also known as library research.